Reescrituras do político: língua italiana x língua dos imigrantes - Parcianello, Juciane Ferigolo (2015)
This thesis studies the political in the language and in the relationship between the languages, considering the space of enunciation of the Associação Italiana de Santa Maria (AISM), designed to "preserve", "protect" the cultural patrimony of Italian immigrants of the Santa Maria region and Quarta Colônia region, and also to promote, develop and teach the Italian language of Italy. We seek, for the theoretical perspective of the Semântica do Acontecimento, from Eduardo Guimarães (2002), analyze the rewriting of designations Italian language, dialect(s), immigrant/Italian/descendant, culture (Italian) and italianity, in the statute text of three institutions: Società Italiana di Mutuo Soccorso e Ricreativa, founded in 1896, in Santa Maria, Sociedade de Cultura Ítalo-Brasileira Dante Alighieri, founded in1985, in the same city, and Associação Italiana de Santa Maria, founded in 1992, in the same place, and successor to the previous Society. The analysis of the semantic functioning of designations exposes the conflicts established mainly between the unequal distribution of places allotted to the Italian language, that in the statutory text of AISM means official language of Italy, language of the great Italian writers, language that should be taught, and to the language of Italian immigrants, whose designation dialect assigned to it means cultural patrimony of immigrants, no place in the teaching. There are many other forms of contradiction in the analyzed texts, but always manifested by differences of meanings and of places with respect to the Italian language and dialect. At this inevitable and irreversible contradiction, which constitutes of enunciation space, Guimarães designates political, and this notion is a displacement of the concept of political from Rancière (2007). Like main scope, through analysis, we intend to answer the following questions:1) which the political meaning of an Italian association that mobilizes the memory of Italian immigration and stands as a representative of immigrants and their descendants? 2) Who and what is this Association representes, and who and what is out of it? 3) What place does the Italian language and the language of immigrants in the space of AISM? The conclusion to which we come, with this study, it is that, in the enunciation space of AISM, the confrontation is between the languages of Italian immigrants and the Italian language from Italy, and not among the languages of immigrants and the national language as happened previously, in the Era Vargas .